EFFECT OF WATER IRRIGATION QUALITY ON POTASSIUM DESORPTION IN SOME CALCAREOUS SOILS IN NINEVH PROVINCE - Mohammed Khalil (Mesopotamia Journal of Agriculture)
A laboratory study was conducted to determine the effect of irrigation water quality on potassium desorption in some calcareous soils. It was constructed by miscible displacement technique using chlorine and sulfuric water via two different textured soils from Fadhlia and Hamdania locations in Nineveh province / northern Iraq for 240 minute with 10 minutes interval at a rate flow 1 ml.minute-1. Results showed higher values of desorbed potassium rate in sulfuric water which were 3.57, 2.128 c.mole.kg-1, while these rates referred to be much lower than that resulted by using chlorine water 2.25, 1.15 c.mole.kg-1 for both locations respectively. Also high correlation appeared between K+ desorption capacity and flow time (R2 = 0.96 , R2 = 0.79) for both water qualities in Fadhlia location , while these rates were (R2 = 0.98, R2 = 0.95) for Hamdania location respectively. Mathematical description for diffusion equation appeared to be of higher values of K+ desorption capacity rates for sulfuric water which were 0.26, 0.13 c.mole.kg-1.min.-½ for Fadhlia and Hamdania locations respectively, while these rates for chlorine water were 0.146, 0.048 c.mole.kg-1.min.-½ for both locations respectively.